Comparative assessment of the impact of molecular scattering and total ozone content on the characteristics of UV radiation in the atmosphere - Melnikova, Irina (International journal of remote sensing, 2009)
The ultraviolet (UV) radiation reaching the Earth's surface has an impact on living organisms, and the beneficial and harmful aspects have been the subject of much discussion. The Earth's atmosphere filters out solar radiation wavelengths less than 280 nm. The atmospheric ozone is the major medium attenuating the UV radiation and is characterized by an inhomogeneous distribution in the atmosphere with a maximum height level of 20-25 km. However, the flux of the UV radiation is also significantly reduced by molecular scattering, whose influence is specifically estimated in this study. In this context, the simplest model of a homogeneous atmosphere is used, considering the six wavelengths 280, 300, 320, 340, 360, 400 nm at two atmospheric pressure levels, 1000 and 500 mb (corresponding on average to altitudes of 0 and 5 km, respectively, above the mean sea level), and three atmospheric ozone levels, normal for summer mid-latitudes plus those decreased by 10% and 50%, respectively. The surface albedo is assumed to be 0 and 0.8 (corresponding to water and snow cover). For the calculations performed, the UV irradiances, the proportion of the scattered light on the surface level and the ratio of the reflected to the transferred irradiance in the atmosphere were considered. In addition, the radiative characteristics of the clear atmosphere were calculated using the Eddington method.